Preserving the digital heritage : principles and policies - de Lusenet, Yola (Netherlands National Commission for UNESCO The HagueNL, 2007)
Highlights the problems and opportunities for long-term preservation of heritage in the digital age. Reviews the current preservation efforts by heritage institutions and proposes various, and sometimes revolutionary, solutions.